TERC haploid cell reprogramming: a novel therapeutic strategy for aplastic anemia - Xinyu Tang; Ruirong Xu; Yan Wang; Kaiqing Chen; Siyuan Cui (BMC, 2023)
Abstract The telomerase RNA component (TERC) gene plays an important role in telomerase-dependent extension and maintenance of the telomeres. In the event of TERC haploinsufficiency, telomere length is often affected; this, in turn, can result in the development of progeria-related diseases such as aplastic anemia (AA) and congenital keratosis. Cell reprogramming can reverse the differentiation process and can, therefore, transform cells into pluripotent stem cells with stronger differentiation and self-renewal abilities; further, cell reprograming can also extend the telomere length of these cells, which may be crucial in the diagnosis and treatment of telomere depletion diseases such as AA. In this study, we summarized the effects of TERC haploid cell reprogramming on telomere length and the correlation between this alteration and the pathogenesis of AA; by investigating the role of cell reprogramming in AA, we aimed to identify novel diagnostic indicators and therapeutic strategies for patients with AA.